Role Of Public Service Advertisements During Covid-19: A Study - Kaur, Navpreet; Sharma, Dr. Trishu (The journal of contemporary issues in business and government, 2021)
Cornoavirus disease-2019 (COVID-19) was announced a "pandemic" by the World Health Organization (WHO) towards the beginning of March 2020 which began spreading from the Wuhan city of China. On worldwide level each nation has taken an unbelievable measure to battle the difficult spread of the continuous episode. In India, the case is most exceedingly terrible as India second on the worldwide file with most elevated number of corona cases. Be that as it may, each state in the underlying stage found a way to battle against the spread of Covid-19. This paper is aimed to dissect the degree of mindfulness and readiness to battle against COVID-19 by the distinctive Indian states through mindfulness crusades.